1.5y+6=

Simple and best practice solution for 1.5y+6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.5y+6= equation:


Simplifying
1.5y + 6 = 0

Reorder the terms:
6 + 1.5y = 0

Solving
6 + 1.5y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 1.5y = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 1.5y = 0 + -6
1.5y = 0 + -6

Combine like terms: 0 + -6 = -6
1.5y = -6

Divide each side by '1.5'.
y = -4

Simplifying
y = -4

See similar equations:

| 2x+9=x^2 | | m+29=-52 | | x-48=-47 | | 7x-3+11x+3=162 | | 3kx^2-2kx+1=0 | | 3.6=r-2.3 | | -4x+6=2x+18 | | a^2-8=26 | | 8.2x+4=7.6x+10 | | x+3=-x-6 | | 64=-2r | | 8.2+4=7.6x+10 | | 9x^2=6-4x | | q+6whenq=12 | | 1-3/5+1/2= | | 2x^2-190x+2400=0 | | 0.50x+0.15(30)=46.5 | | -9c-5=13 | | z-7=14 | | -7=m(-6)+b | | 42+m=-21 | | -36+f=4 | | -2+3x=4x-7-x | | -1/2(6x+9)-(x-3/2)= | | 2+x=-(x+6) | | 2(13x-15)+3(x-19)=0 | | 2x+5+3x=15 | | h+4=-3 | | -4(3y-6)-y=-3(y-4) | | 2x^2-22x+28.5=0 | | 16+z=14 | | (x^2)-2x-35=0 |

Equations solver categories